ECOLOGICAL METHODOLOGICAL SYSTEM FOR THE DEVELOPMENT OF CULTURE IN THE TEACHING OF BIOLOGY - I. Usmanov (Galaxy International Interdisciplinary Research Journal, 2023)
The need for the formation of an ecological worldview of the medodic system of development of the ecalogical culture of Ukers in biology uktitsh during the renewal processes of today's educational system is a requirement of the period. The article expresses the possibilities of implementing this demand through society, state and educational institutions. Together with this, ecologist Culture Development views of Eastern thinkers, examples of views presented in religious sources are cited.